2017
DOI: 10.1021/acsami.6b13351
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanospheres-Stabilized Indocyanine Green as a Synchronous Photodynamic–Photothermal Therapy Platform That Inhibits Tumor Growth and Metastasis

Abstract: Both photothermal therapy (PTT) and photodynamic therapy (PDT) are phototherapeutic approaches, which have been widely investigated for cancer therapy mediated by an external light source. Here, a nanosystem presenting the synchronous PTT and PDT effect realized through one-step near-infrared (NIR) light irradiation is reported. This system was fabricated by conjugating indocyanine green (ICG) on hollow gold nanospheres (HAuNS) using branched-polyethylenimine (PEI, MW = 10 kDa) as optimal linker, which provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…[324][325][326][327][328][329] Synergistic surgery with multimodal ablations have been expected to achieve high antitumor efficacy and good surgical outcomes. [324][325][326][327][328][329] Synergistic surgery with multimodal ablations have been expected to achieve high antitumor efficacy and good surgical outcomes.…”
Section: Other Synergistic Surgerymentioning
confidence: 99%
“…[324][325][326][327][328][329] Synergistic surgery with multimodal ablations have been expected to achieve high antitumor efficacy and good surgical outcomes. [324][325][326][327][328][329] Synergistic surgery with multimodal ablations have been expected to achieve high antitumor efficacy and good surgical outcomes.…”
Section: Other Synergistic Surgerymentioning
confidence: 99%
“…However, these organic molecules possess poor physiological stability, which impeded their clinical application. With the assistance of nanotechnology, nanocomposites were introduced to overcome the shortcoming . Guo et al.…”
Section: Deep Pdtmentioning
confidence: 99%
“…With the assistance of nanotechnology, nanocomposites were introduced to overcome the shortcoming. [43][44][45] Guo et al reported a cypate and Chlorin e6 (Ce6) co-loaded micelle system for imaging-guided photodynamic /photothermal therapy (PTT) ( Figure 1). [46] The system exhibited enhanced photostability, cellular uptake and tumor accumulation.…”
Section: Nir Light Excited Deep Pdtmentioning
confidence: 99%
“…However, the poor stability restricted the usage of ICG in clinic. Several nanostructures were introduced to overcome the limitation (Gao et al, ; Khatri et al, ; Li et al, ; Shemesh, Moshkelani, & Zhang, ; Sun et al, ). Recently, Hu et al combined hydroxyethyl starch‐oleic acid conjugate based nanoparticles with β‐Phenylethyl isothiocyanate to encapsulate ICG.…”
Section: Nanocarriers Used In Deep Pdtmentioning
confidence: 99%